Anemia and its determinants among adolescent girls in Southern Ethiopia - Yoseph Halala Handiso (Taylor & Francis Group, 2022)
Adolescence is defined as the age range of 10-19 years and it is a transition period from childhood to adulthood. Adolescent girls are vulnerable especially to iron deficiency due to accelerated increase in requirements for iron, poor dietary intake of iron, menstrual losses, infection, norm of early marriage, and adolescent pregnancy. The aim of this study is to assess anemia status and its determinants among adolescent girls in Southern Ethiopia. This research was done in Southern Nations, Nationalities, and Peoples' Region (SNNPR). Community-based cross-sectional study was conducted from April 30/2019 to May 30/2019. A multistage sampling method was used to select a sample of 843 adolescent girls. Pre-testing of the questionnaire was done on 5% adolescent girls to ensure the reliability of the questionnaire. Finger prick blood sample was collected from all adolescent girls. Hemoglobin level was measured in finger-prick blood samples using a Hemocue photometer which was processed in the field (Hemocue R, Hb 301+ system. Data were entered in the computer using EPI-data version 4.4.2 and exported to SPSS version 21.0 for further analysis. Variables which showed association (p-value ≤ 0.25) in the bivariate logistic analysis were included in the final multivariable logistic regression model. Odds ratios for logistic regression along with 95% confidence interval were estimated. P-values less than 0.05 were declared as level of statistical significance. 820 adolescent girls were participated with a response rate of 97.3. The mean (± SD) blood hemoglobin level of the study participants was 12.23 ± 1.16 g/dL and 37% of the study participants are moderately anemic (Hg 7-12 gm/dl) and 0.2% of the study participants are severely anemic (Hg < 7 g/dL). Overall prevalence of anemia was 37.2% among adolescent girls in the study area. Family monthly income, illness with cough, and malaria in the past two weeks, skipping regular meals, and BMI-for-age are the main predictors of low blood hemoglobin level among adolescent girls in southern Ethiopia. Thus, community-based Iron folic acid supplementation and deworming tablet intervention program should be implemented to help adolescent girls who are at risk of anemia. In addition to these, malaria prevention mechanism and improving family monthly income program should be implemented.